Oxidative Stress on Buccal Mucosa Wound in Rats and Rule of Topical Application of Ethanolic Extracts of Mauli Banana (Musa acuminata) Stem - Wenda Fitriati Noor; Novie Aprianti; Saldy Rizky Saputra; Maharani Laillyza Apriasari; Eko Suhartono (Journal of Tropical Life Science, 2015)
The present study was undertaken to evaluate the effect of a topical application of ethanolic extracts of Mauli banana stem on buccal mucosa wounds in rats (Rattus novergicus). Three sets of experiments with 3 groups male rats each consisted of 9 animals were used for studying wound oxidative stress status. Group 1 (P0) as the negative control was left to heal spontaneously; group 2 (P1) as the postive control were treated with alocair topically; and group 3 (P2) as treatment group were treated with ethanloic extracts of Mauli banana stem topically, respectively, 24h after wound creation for 3 days. The oxidative stress status was evaluated by monitoring the SOD, CAT activity, MDA and CC levels. The effect of ethanolic extracts of Mauli banana stem on oxidative stress status revealed significant increased in SOD activity, decreased in MDA levels, and no significant change both in CAT activity and CC levels compared to negative control. These results showed that The ethanolic extracts of Mauli banana stem might affect the oxidative stress status during wound healing process. Key Word : Antioxidant, Free Radicals, Mauli banana, Oxidative Stress, Wound Healing.